2004
DOI: 10.1080/00365590410025497
|View full text |Cite
|
Sign up to set email alerts
|

Role of i.v. urography in patients with haematuria

Abstract: In this cohort of retrospectively studied patients attending a haematuria clinic, IVU could safely have been omitted without decreasing the overall detection of malignant pathologies. Nevertheless, significant non-malignant pathologies would have remained undiagnosed. The authors suggest that US combined with a MAG III renogram could be considered as a first-line investigation instead of IVU. This is likely to result in maximum detection of malignant and non-malignant conditions, while reducing the radiation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Among the population-screening studies cited in the AUA guideline, only 1 patient younger than 40 years was clearly reported to have GU cancer 56 ; an additional study reported 1 case of bladder cancer among 30 patients with MH, although this patient's age was not reported. 57 Among 40 referral studies of patients undergoing evaluation for MH, 4 studies clearly identify 6 patients younger than 40 years with GU cancer diagnoses [58][59][60][61] (although 3 of these 4 studies do not provide specific ages) and an additional 15 studies report cancer diagnoses but do not specify whether they occurred in patients younger than 40 years. 23,[62][63][64][65][66][67][68][69][70][71][72][73][74][75] Although a handful of these studies comment on the role of cigarette smoking, none systematically account for all known GU cancer risk factors.…”
Section: Existing Guidelines and Recommendationsmentioning
confidence: 96%
“…Among the population-screening studies cited in the AUA guideline, only 1 patient younger than 40 years was clearly reported to have GU cancer 56 ; an additional study reported 1 case of bladder cancer among 30 patients with MH, although this patient's age was not reported. 57 Among 40 referral studies of patients undergoing evaluation for MH, 4 studies clearly identify 6 patients younger than 40 years with GU cancer diagnoses [58][59][60][61] (although 3 of these 4 studies do not provide specific ages) and an additional 15 studies report cancer diagnoses but do not specify whether they occurred in patients younger than 40 years. 23,[62][63][64][65][66][67][68][69][70][71][72][73][74][75] Although a handful of these studies comment on the role of cigarette smoking, none systematically account for all known GU cancer risk factors.…”
Section: Existing Guidelines and Recommendationsmentioning
confidence: 96%